PENGELOLAAN PRODUKSI USAHA BORDIR BUKITTINGGI (Studi Kasus Pada Usaha Bordir Ambun Suri) - Febriani, Reka; Zahri, Wildati; Idrus, Yenni (Journal of Home Economics and Tourism, 2015)
This study describes how the business premises Ambun Suri manage production so much in demand, this study aims to obtain information, analyze and describe data tentangpengelolaan Ambun Suri production embroidery business as workforce planning, tools and raw materials, and production planning.The method used in this study is a qualitative case study method. This research was conducted in the city of Bukittinggi. The type of data in the form of primary data and secondary data. Data collection was done by observation, interviews, and documentation. Data analysis techniques used are data reduction means summarizing key points in accordance with the focus of research, the presentation of the data is done in the form of a brief description, and conclusions mentioned here can answer the problem formulation. To get valid data to perform data validity extended way back spaciousness observation point researchers to obtain additional discovery, increase endurance, triangulation and auditing.Results of research on the management of the production of embroidery, namely: (1) planning workforce consisting of recruitment is done in non-formal, planning work time in a place of business Ambun Suri 5 days a week and remuneration planning tailored to the work or how much finished materials embroidered (2) planning tool starts from planning sewing machine, sewing needle, thread and material used starting from planning its kind and many are used in production. (3) for the planning of production starting from the planning motifs, decorative patterns, embroidery process to distribute it.Kata kunci : Pengelolaan Produksi Bordir Bukittinggi